2004
DOI: 10.1103/physrevlett.92.017602
|View full text |Cite
|
Sign up to set email alerts
|

Dome-Shaped Magnetic Phase Diagram of Thermoelectric Layered Cobaltites

Abstract: Using muon spin spectroscopy we have found that, for both NaxCoO(2) (0.6 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 22 publications
2
85
1
Order By: Relevance
“…Although crude magnetic-phase mappings in this range before suggest that T N varies between 22-27 K, 3,14 Schulze et al recently found an additional 8 K phase for x ϳ 0.80 and 0.85, which can be obtained only after a slow cooling process. 10 With carefully tuned single crystals in the narrow range of 0.82-0.86, we are able to revisit the magnetic-phase diagram and untangle the mystery of T N variation.…”
Section: Resultsmentioning
confidence: 99%
“…Although crude magnetic-phase mappings in this range before suggest that T N varies between 22-27 K, 3,14 Schulze et al recently found an additional 8 K phase for x ϳ 0.80 and 0.85, which can be obtained only after a slow cooling process. 10 With carefully tuned single crystals in the narrow range of 0.82-0.86, we are able to revisit the magnetic-phase diagram and untangle the mystery of T N variation.…”
Section: Resultsmentioning
confidence: 99%
“…[28,29,30] In most misfit-layered triangular cobaltitles, such as Ca 3 Co 4 O 9 , (Bi,Pb) 2 M 2 Co 2 O y (M =Ca and Sr), SDW is a common spin ordered state. [10] Determining from the µSR results, however, no SDW exists down to 1.8 K at zero or low field in updoped Bi 2 Ba 2 Co 2 O y , [10] Another point of view is the weak localization in 2D systems, [31,32] which theoretically predicts a logarithmic temperature dependence of the conductivity. [33] The misfit structure leads to the system to be 2-dimensional structurally.…”
Section: Discussionmentioning
confidence: 99%
“…[1, 2, 3, 4] The complex physical properties include the unconventional superconductivity in water-intercalated Na 0.35 CoO 2 , [5] temperature-dependent Hall effect, [3,6] large negative MR in (Bi,Pb) 2 M 2 Co 2 O y (M=Sr and Ca) and Ca 3 Co 4 O 9 ,[2, 6,7] large thermopower (TEP) with low resistivity,[1, 2] and complicated magnetic structure, [8,9,10] etc. These triangular cobaltites have the common structural unit of CdI 2 -type hexagonal [CoO 2 ] layer, which is composed of edge-shared CoO 6 octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,3,4,5] Several researchers reconfirmed later the existence of long-range magnetic order in the layered cobaltites by not only µ + SR [6] but also neutron diffraction experiments. [7] These cobaltites share a common structural component as a conduction path, i.e., the CoO 2 planes, in which a two-dimensional-triangular lattice of Co ions is formed by a network of edge-sharing CoO 6 octahedra.…”
Section: Introductionmentioning
confidence: 93%